Swab Bukal Sebagai Bahan Sexing Piyikan Burung Kenari (Serinus canaria) dan Burung Merpati (Columba livia) - Akrom, Afif Muhammad; Indarjulianto, Soedarmanto; Yanuartono, Yanuartono; Susmiati, Trini; Nururrozi, Alfarisa; Raharjo, Slamet; Permana, Rief Ghulam Satria; Sitompul, Yeremia Yobelanno (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2020)
Molecular sexing for bird with polymerase chain reaction-based method have been developed, but the samples used as a sources of DNA are blood and feathers which are considerably invasive. The aim of this study was to study the efficiency of buccal swabs as a resource of DNA for sexing canary bird and pigeon. This study used 10 canaries (Serinus canaria) consisting of 6 adult canaries (3 males and 3 females) and 4 young nestling canaries (14 - to 18-day old) and 6 adults (3 males and 3 females) pigeons (Columba livia) and 7 young nestling pigeons (14- to 25-day-old). All birds were taken their buccal swab samples, then DNA were extracted, mixed with PCR-mix to be amplified for sexing genes with CHD1F/CHD1R primer pairs. The amplification results showed that all of adult male birds produced single band (± 500 bp), whereas all of adult female birds produced double bands (± 500 bp and ± 300 bp). The PCR method for nestling canaries showed 2 males and 2 females. whereas nestling pigeons 6 males and 1 female. Based on this study it can be concluded that buccal swabs are efficient as a source of DNA for birds sexing especially young nestling birds.